Age estimation using comprehensive chart for dental age estimation in Haryana population: A pilot study - Cheena Singh; Kusum Singal; Priyanka Kapoor (Wolters Kluwer Medknow Publications, 2018)
Background: Dental age estimation by radiographic methods for forensic rationale is routinely applied to serve the judicial system. Of these, Demirjian system is most widely used, but its applicability in the Indian population, specifically Haryana population, is still lacking. Aim and Objective: This is a pilot study to evaluate Demirjian method in Haryana population using a comprehensive chart for dental age estimation (DAEcc) and establish a correlation between the chronological age (CA) and estimated age. Materials and Methods: Sample comprised 100 subjects (49 males and 51 females) 7-16 years of age. Orthopantomograms of these patients were traced and evaluated for Demirjian dental age computation using DAEcc and compared with CA. Results: A positive correlation was observed between CA and estimated age (R2 = 0.82 in males, R2 = 0.78 in females, and R2 = 0.80 in combined population). The paired t-test between CA and estimated age demonstrated that Demirjian method underestimates the dental age by 5.1 months, that is, 153 days in males (P = 0.04) and by 7.9 months, that is, 237 days in females (P = 0.01). There was an overall underestimation by 6.3 months (P = 0.001) in the entire study population. Conclusion: This pilot study supports the applicability of Demirjian method for age estimation in Haryana population and paves way for further studies in a larger sample in the same population to accurately establish the association between CA and dental age.